Representation of a Human Body: A Comparison Study between Balinese and Javanese Traditional House - Anak Agung Ayu Wulandari; Ade Ariyani Sari Fajarwati (Bina Nusantara University, 2020)
The research would look further at the representation of the human body in both Balinese and Javanese traditional houses and compared the function and meaning of each part. To achieve the research aim, which was to evaluate and compare the representation of the human body in Javanese and Balinese traditional houses, a qualitative method through literature and descriptive analysis study was conducted. A comparative study approach would be used with an in-depth comparative study. It would revealed not only the similarities but also the differences between both subjects. The research shows that both traditional houses represent the human body in their way. From the architectural drawing top to bottom, both houses show the same structure that is identical to the human body; head at the top, followed by the body, and feet at the bottom. However, the comparative study shows that each area represents a different meaning. The circulation of the house is also different, while the Balinese house is started with feet and continued to body and head area. Simultaneously, the Javanese house is started with the head, then continued to body, and feet area.